Vascular flora and vegetation of Ica valley, Peru - Roque, José (1999)
The vascular flora and vegetation were studied in the valley of Ica, located in the central coast of Peru. A total of 142 species were registered, from 121 genera and 39 families. Magnoliopsid (dicotyledons) represented 79% of the species, liliopsids (monocotyleclons) 20%, and Ptericlophyta only 1%. Herbs were the prevalent growth form (80% of the species), while riverine environments and agricultural fields were the preferred habitats for most of the species. This study expands the known distributions of 46 species, three of which are endemic to Peru.